Cultivating Diversity: Multicultural Representation in Collection Development at Tumbuh 2 Elementary School, Yogyakarta - Astari, Isna Windi; Marwiyah, Marwiyah (Librarianship in Muslim Societies, 2024)
SD Tumbuh 2 prioritizes multiculturalism, necessitating the integration of multicultural values throughout its curriculum, school environment, and library resources. In terms of library services, the development of library collections is fundamental, necessitating the school's diligent engagement in collection development activities to ensure their proper curation and enhancement. Hence, it is imperative to address how multicultural values are infused into the collection development process within the library of SD Tumbuh 2. This research aims to explore the manifestation of multiculturalism values within the collection development practices at Tumbuh 2 Elementary School Library in Yogyakarta. Employing a qualitative method with a descriptive approach, the study focuses on the Tumbuh 2 Elementary School Library as the subject, examining how multiculturalism values are represented in its collection development practices. The research employs a combination of data collection techniques, including non-participant observation, semi-structured interviews, and documentation. Data analysis follows Miles and Huberman's model, comprising reduction, data display, and verification stages to ensure comprehensive examination and validation of findings.The findings of this study reveal that the collection development practices at Tumbuh 2 Elementary School in Yogyakarta effectively reflect multiculturalism values. These findings underscore the school's commitment to fostering an environment that aligns with its vision and mission, demonstrating a coherent approach to promoting diversity and inclusivity within its educational framework. The portrayal of multiculturalism values in the collection development practices at the library reflects an ethos of inclusivity, characterized by openness and a commitment to fostering dialogue. Furthermore, it embodies humanistic principles, tolerance, democratic ideals emphasizing justice, and egalitarianism, thereby promoting equality within the school community.